Electromagnetic band gap (EBG) structure incorporated with microstrip antenna [electronic resource] - 432910 Akram Hadi Ali Lawar (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Sarjana Kejuruteraan (Elektrik - Komunikasi)) - Universiti Teknologi Malaysia, 2008